The Relationship Between Health Literacy With Confidence and Self-Efficacy in Arv Treatment in People With Hiv/Aids in Hospital - Asroful Hulam Zamroni; Nursalam Nursalam (Universitas Pahlawan Tuanku Tambusai, 2026)
Adherence to antiretroviral (ARV) treatment in people with HIV/AIDS (ODHA) is shaped by the confidence and self-efficacy of ODHA in undergoing ARV therapy, which ultimately affects treatment success. This study aimed to analyse the relationship between health literacy, health beliefs, and self-efficacy in ARV treatment in ODHA in hospitals. This quantitative study with a cross-sectional design involved a sample of 160 ODHA patients undergoing ARV therapy at Hospital X, selected using a purposive sampling technique. Data were collected using a structured questionnaire that was tested for validity and reliability. Bivariate analysis was conducted using the chi-square test to assess the relationship between health literacy, health confidence, and self-efficacy. The results showed a significant relationship between health literacy and health confidence (p = 0.001) and self-efficacy (p = 0.002). Respondents with high health literacy mostly had health confidence and self-efficacy in the medium to high categories, while respondents with low health literacy tended to be in the low confidence and self-efficacy categories. Health literacy was significantly related to the confidence and self-efficacy of ODHA undergoing ARV treatment. Increasing health literacy, which is integrated with strengthening confidence and self-efficacy, is needed to support treatment adherence and improve the quality of life of ODHA.